Efficient optical plasmonic tweezer-controlled single-molecule SERS characterization of pH-dependent amylin species in aqueous milieus - Wenhao Fu; Huanyu Chi; Xin Dai; Hongni Zhu; Vince St. Dollente Mesias; Wei Liu; Jinqing Huang (Nature Communications, 2023)
Abstract It is challenging to characterize single or a few biomolecules in physiological milieus without excluding the influences of surrounding environment. Here we utilize optical plasmonic trapping to construct a dynamic nanocavity, which reduces the diffraction-limited detection volume and provides reproducible electromagnetic field enhancements to achieve high-throughput single-molecule surface-enhanced Raman spectroscopy (SERS) characterizations in aqueous environments. Specifically, we study human Islet Amyloid Polypeptide (amylin, hIAPP) under different physiological pH conditions by combining spectroscopic experiments and molecular dynamics (MD) simulations. Based on a statistically significant amount of time-dependent SERS spectra, two types of low-populated transient species of hIAPP containing either turn or β-sheet structure among its predominant helix-coil monomers are characterized during the early-stage incubation at neutral condition, which play a crucial role in driving irreversible amyloid fibril developments even after a subsequent adjustment of pH to continue the prolonged incubation at acidic condition. Our results might provide profound mechanistic insight into the pH-regulated amyloidogenesis and introduce an alternative approach for investigating complex biological processes at the single-molecule level.